General Trends of Comparative Linguistic Cognitive Science. / Tendencias generales de la ciencia cognitiva lingüística comparativa. - LILIIA, GABITOVA; LEYSAN, SHAYAKHMETOVA; ZHARKYNBEKOVA, SHOLPAN (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The paper examines the main trends in the development of comparative linguistic, cognitive science; it analyzes the preconditions for the formation of this direction, and highlights the prospects and challenges for its further development. The authors emphasize that comparative linguo-cognitive studies open up new horizons for bilingual lexicography, in particular, to create a model of a new type dictionary. Active development of theoretical and methodological foundations of general and comparative linguistics, linguistic-cultural studies, pragmatic linguistics and linguistic didactics have formed a basis for the theoretical understanding of many provisions of cognitive linguistics. RESUMEN El artículo examina las principales tendencias en el desarrollo de la ciencia cognitiva lingüística comparada; analiza las condiciones previas para la formación de esta dirección y destaca las perspectivas y desafíos para su desarrollo posterior. Los autores enfatizan que los estudios comparativos lingüístico-cognitivos abren nuevos horizontes para la lexicografía bilingüe, en particular, para crear un modelo de un nuevo tipo de diccionario. El desarrollo activo de los fundamentos teóricos y metodológicos de la lingüística general y comparada, los estudios culturales lingüísticos, la lingüística pragmática y la didáctica lingüística han formado una base para la comprensión teórica de muchas disposiciones de la lingüística cognitiva.